2016
DOI: 10.1097/md.0000000000002588
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination is Associated with Lower Risk of Acute Coronary Syndrome in Elderly Patients with Chronic Kidney Disease

Abstract: Elderly patients with chronic kidney disease (CKD) are at a higher risk of hospitalization for cardiovascular diseases (CVD). Previous studies have showed that influenza vaccination could reduce the risk of recurrent major cardiovascular events in patients with CVD. However, the effects of influenza vaccination on the reduction of first hospitalizations for acute coronary syndrome (ACS) in elderly patients with CKD remain unknown.We conducted a cohort study using data from the Taiwan Longitudinal Health Insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…In addition, such costs need to be set against the substantial direct saving that will potentially be achieved. Some vaccination studies have already reported a reduction in hospitalization rates greatly exceeding 50% in older patients with comorbidities [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, such costs need to be set against the substantial direct saving that will potentially be achieved. Some vaccination studies have already reported a reduction in hospitalization rates greatly exceeding 50% in older patients with comorbidities [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Over the 18-month study period, participants receiving both vaccines saw significant reductions in coronary and intensive care admissions of 41 and 55%, respectively [14]. Population-based cohort studies on older adults (> 55 years) with comorbidities that put them at risk for cardiovascular disease found a clear association Gerontology 2020;66:238-248 DOI: 10.1159/000503141 between decreased risk of acute coronary syndrome hospitalization and influenza vaccination [15,16]. The vaccine caused an overall reduction in hospital admissions of 56% for acute coronary syndromes for patients with chronic obstructive pulmonary disease, and 65% for patients with chronic kidney disease (CKD) [15,16].…”
Section: Vaccination As a Tool For Maintaining Wellnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is the risk that acutebut treatableinfections may have more sequelae in older patients. These include loss of function, and increasing risk of frailty (itself a risk factor for subsequent infections) which is associated with elevated risk for CVD and diabetes [91][92][93]. The goal of life-course immunization, and of the healthy aging agenda in general, is to prevent this downward spiral in older individuals.…”
Section: Beyond Infectious Diseasevaccination As An Important Tool Fomentioning
confidence: 99%
“…A number of recent studies have shown influenza infection to be a potential trigger for cardiovascular conditions including acute coronary syndromes [95][96][97], and atrial fibrillation [98], with some studies showing that influenza vaccination can lower risk of acute cardiovascular events and mortality in patients with medical co-morbidities [89,92,[98][99][100][101], and others demonstrating an association between influenza vaccination and a reduction in hospitalisations and deaths due to heart failure [102][103][104][105]. In their study evaluating the benefits of influenza and pneumococcal vaccination in individuals aged !65 years, Hung et al found that while both vaccines reduced the risk of ischemic stroke, myocardial infarction and coronary care admissions, benefit was greatest in those receiving both vaccines [106].…”
Section: Beyond Infectious Diseasevaccination As An Important Tool Fomentioning
confidence: 99%